Rhetorical structure in the problem statement section of Iranian postgraduate students' research projects - Zahra Tarvirdizdeh; Vahid Nimehchisalem (Universitas Syiah Kuala, 2021)
This paper reports the results of a study that investigated the structure of the Problem Statement (PS) section, following Swales’ (1990) Create-A-Research-Space (CARS) model as the first objective. Move analysis was used to analyze the rhetorical moves of the PS sections of the research projects. The second objective was the identification of the specific types of linguistic features associated with each move and step based on Pho’s (2013) classification. Following Pho (2013), the linguistic features as important signals of moves were identified. For this purpose, 30 research projects written by Iranian master’s students were purposively selected. The findings showed that the obligatory moves were Moves 1 ‘Establishing a Territory’ and 2 ‘Establishing a Niche’. All moves and steps were identified linguistically although their sequence and arrangement were not the same as what was anticipated by the model. Although the cyclic and embedded moves were defined in the rhetorical structure of the PSs, most of them were anomalous or ill-structured. The study has theoretical contributions, the most significant one of which is that the CARS model is applicable to define and analyze the rhetorical structure of the PS section.